The effects of planning conditions on Chinese primary school ESL pupils’ narrative writing / Ma Fei Fan - Ma, Fei Fan (2016)

(untitled)
The present study investigates how 78 pupils from a Chinese primary school in the state of Selangor performed differently in their second language writing under different planning conditions in terms of the language complexity, accuracy and fluency (CAF). Besides, the study also aims to examine the pupils’ perceptions of their own performance under different planning conditions and how these perceptions are related to their performance. Drawing from Kellogg’s (1996) model as the theoretical framework, this study also seeks to describe how pupils perform their narrative writing task mentally. The pupils were divided into three planning condition groups:1) pre-task planning, 2) on-line planning and 3) no planning groups. A variety of data collection methods had been employed in order to obtain pupils’ data. These methods include the collection of pupils’ written task and pupils’ planning sheets, questionnaire surveys and interview. The results of the study reveal that pupils’ performance was not significantly affected by the planning conditions except for the effect of pre-task planning on pupils’ written fluency. The results discovered from the present study differ greatly from many of the previous studies which were mainly carried out on adult writers. The present study also discovers that pupils’ perceptions partially influence their performance. The reasons of such contradictions are discussed in the discussion section in this article. Keywords: second language writing, complexity, accuracy, fluency, Kellogg’s (1996) model.